Removal of tetracycline and oxytetracycline by microscale zerovalent iron and formation of transformation products - Hanay, Ozge; Yildiz, Burcin; Aslan, Sibel; Hasar, Halil (Springer Heidelberg, 2014)
The main objective of this study was to determine the removal mechanism of tetracycline (TC) and oxytetracycline (OTC) by microscale zerovalent iron (mZVI) and the formation of transformation products during their removal studies. Solution pH, iron dose, and reaction temperature were studied with a batch experimental series in order to evaluate the removal efficiency of TC and OTC and the adsorption kinetics. The results showed that pH was a key factor in removing both tetracycline compounds, although increasing the temperature and iron dose enhanced their removal efficiency. The optimal pH was similarly found as 3 for both tetracycline and oxytetracycline. The kinetics of adsorption fitted the pseudo-second-order model perfectly. The adsorption data was interpreted by the Langmuir model with the maximum adsorption capacity of 23.98 and 34.01 mg g(-1) (60 A degrees C) of TC and OTC on mZVI, respectively. The main transformation product was 4-epi-tetracycline for TC which quickly sorbed onto mZVI within 15 min. beta-Apo-OTC and alpha-Apo-OTC were found as OTC transformation products. The removal mechanism of TC and OTC using mZVI surface was due to the adsorption rather than the degradation process.
Keywords: Tetracyclines; Transformation product; Adsorption kinetic; Microscale zerovalent iron